Strategic market management - Aaker, David A. (New York : John Wiley and Sons, 1995)
This book is about: Introduction and overview; External analysis; Internal analysis; Alternative business strategies; Implementation and the planning process; ...
Keywords: Marketing; Management; Marketing -- Management